Analysis of Mutation Spectra of 28 Pathogenic Genes Associated With Congenital Hypothyroidism in the Chinese Han Population - Huang, Miao; Lu, Xiyan; Dong, Guoqing; Li, Jianxu; Chen, Chengcong; Yu, Qiuxia; Li, Mingzhu; Su, Yueyue (Frontiers in Endocrinology, 2021)
Purpose Congenital hypothyroidism (CH) is the most common neonatal endocrine disease; its early detection ensures successful treatment and prevents complications. However, its molecular etiology remains unclear. Methods We used second-generation sequencing to detect 28 pathogenic genes in 15 Chinese Han patients with CH in Shenzhen, China, and analyzed the genetic pattern of the pathogenic genes through their pedigrees. The pathogenicity assessment of gene mutations was performed based on the American College of Medical Genetics and Genomics (ACMG) classification guidelines, inheritance models, and published evidence. Results Mutations in several target genes were identified in 14 of 15 patients (93.33%); these mutations were distributed in eight genes (DUOX2, DUOXA2, TPO, TG, TSHR, FOXE1, KDM6A, and POU1F1). DUOX2 exhibited the highest mutation frequency (44%, 11/25), followed by TPO (16%, 4/25) and TG (16%, 4/25). DUOX2 exhibited the highest biallelic mutation (7/15). Eight out of 25 variants verified by the ACMG guidelines were classified as pathogenic (P, category 1) or possibly pathogenic (LP, Type 2), namely six variants of DUOX2, and one variant of TPO and DUOXA2. Five new mutations were detected: one in DUOX2, which was located in the splicing region of mRNA (c.1575-1G>A), three new missense mutants, p.A291T, p.R169W, and p. S1237dup, and one new TPO missense variant c.2012G>T (p.W671L). The main criteria for determining the genotype–phenotype relationship were a diagnostic detection rate of 53.33% (8/15) and combination of three or more gene mutations. Conclusions CH gene mutations in the population may be mainly manifested in genes influencing thyroid hormone synthesis, such as DUOX2 compound heterozygous mutations, which exhibited a high detection rate. The clinical manifestations are diverse, and mainly include transient CH. Therefore, genetic screening is recommended for CH patients to determine the correlation between clinical phenotypes and gene mutations, which will assist in clinical management.